Ferroelectric seeds-induced phase evolution and large electrostrain under reduced poling field in bismuth-based composites. Issue 11 (1st August 2018) - Khaliq, Abdul; Sheeraz, Muhammad; Ullah, Aman; Seog, Hae Jin; Ahn, Chang Won; Kim, Tae Heon; Cho, Shinuk; Kim, Ill Won
Abstract: Bi0.5 Na0.5 TiO3 -based piezoelectric ceramics have attracted great interest in actuator applications due to their high strain response; however, high driving field and large hysteresis of these materials are long-lasting obstacles for their commercial applications. Here, we use a strategy to overcome these hurdles by reducing poling field of the relaxor 0.96Bi0.5 (Na0.78 K0.22 )0.5 TiO3 -0.04Bi(Mg0.5 Ti0.5 )O3 (BNKT-0.04BMT) matrix introducing ferroelectric (BNT, BKT and BNKT) seeds (10, 15 and 20 wt%). The poling field decreases with increasing ferroelectric seeds accompanied by the transformation from ergodic relaxor to ferroelectric phase. Consequently, large normalized strains (d * 33 = Smax /Emax = 560, 469 and 450 pm/V) were recorded for BNT (15 wt%), BKT (10 wt%) and BNKT (15 wt%) seeded composites under a reduced driving field of 2.5 kV/mm. These findings indicate that ferroelectric seeds are more effective in reducing the field for strain activation which can be appropriate for actuator devices.